Faculty perceptions of academic librarians at the University of the Philippines Diliman - Visperas, Rizalyn S. (Institute of Library Science, University of the Philippines Diliman, 2002)
This study sought to determine the perceptions of the faculty of the University of the Philippines (UP) Diliman College of Arts and Letters (CAL) and College of Social Sciences and Philosophy (CSSP) towards academic librarians. The respondents in this study were full-time and part time faculty of these two colleges during the second semester of the school year 2001-2002. Results of the study reveal that the faculty rate the librarians efficient enough in keeping the faculty informed on changes in the library; efficient in keeping the faculty informed of new publications in their respective disciplines; and in assisting them in searching for materials in their subjects of expertise. A majority also perceived that librarians in general contribute only 30 percent in the education of the students.